SISTEM PENDUKUNG KEPUTUSAN BERBASIS AHP (ANALYTICAL HIERARCHY PROCESS) UNTUK PENENTUAN KESESUAIAN PENGGUNAAN LAHAN (STUDI KASUS: KABUPATEN SEMARANG) - Sri Hartati; Adi Nugroho (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
The determination of landsuitability (residential, industrial, forestry, recreation, and waste disposal sites) in a given area need the attention of decision makers at both the central and local levels. Various parameters (roads, slope, water availability, etc.) should be considered carefully so that decision makers can make a qualified decision-making. In this paper, we chose AHP (Analytical Hierarchy Process) as a method to be used as a basis for decision making. In this case, GIS (Geographical Information System) which is able to visualize a particular geographic area can be used show the AHP’s calculation results to a computer screen or in the printed maps.